Pengaruh Model Pembelajaran Problem Posing Berbasis Video Canva Terhadap Hasil Belajar Ekonomi Siswa Kelas XI Di SMA Negeri 13 Medan - Br. Limbong, Mika Jun Fera; Yuni, Revita (Universitas Batanghari Jambi, 2026)
This research aims to determine the effect of Problem Posing learning model based on Canva video on economics learning outcomes of grade XI students at SMA Negeri 13 Medan. The study employs quantitative methodology with quasi-experimental pretest-posttest control group design. The sample consisted of 72 students selected through purposive sampling, comprising 36 students in the experimental group (class XI-4) and 36 students in the control group (class XI-1). The research instrument was a validated 30-item multiple-choice test on Monetary Policy content delivered across three instructional sessions. Research findings reveal substantial improvements in the experimental group with average scores increasing from 58.92 to 85.36, while the control group showed moderate improvement from 56.47 to 78.39. Statistical analysis using independent sample t-tests yielded a significance value of 0.002 (p < 0.05), confirming significant positive effects of Problem Posing learning model based on Canva video on student economics learning outcomes. Observational data indicates 80.5% of experimental group students achieved excellent performance levels compared to 25% in the control group. The Problem Posing learning model based on Canva video proves effective in improving both academic achievement and student engagement in economics education.